2019
DOI: 10.1111/sjop.12551
|View full text |Cite
|
Sign up to set email alerts
|

Honesty‐humility and prosocial behavior: The mediating roles of perspective taking and guilt‐proneness

Abstract: The prosocial personality trait of honesty‐humility has received extensive attention in the last decade. However, research on the mechanism underlying the relationship between honesty‐humility and prosocial behavior is rather scarce. This study aims to explore the internal mechanism underlying this relationship to draw a complete picture of the honesty‐humility trait. A sample of 458 Chinese young adults was obtained to complete self‐report measures of honesty‐humility, perspective taking, guilt‐proneness, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…Third, although we found that moral disengagement signiicantly mediated the association between Honesty-Humility and unethical behavior, we are not yet able to fully elucidate the underlying mechanisms of this relationship. It is important that future research examines other potential mediators, for instance, perspective taking and guilt-proneness (e.g., Fang, Dong, & Fang, 2019). Fourth, we measured unethical behavior through hypothetical scenarios based on participants' self-reports.…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 99%
“…Third, although we found that moral disengagement signiicantly mediated the association between Honesty-Humility and unethical behavior, we are not yet able to fully elucidate the underlying mechanisms of this relationship. It is important that future research examines other potential mediators, for instance, perspective taking and guilt-proneness (e.g., Fang, Dong, & Fang, 2019). Fourth, we measured unethical behavior through hypothetical scenarios based on participants' self-reports.…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 99%
“…Yet, there is a lack of research involving nonprofit advertising. Given the prosocial context of NPOs, the Honesty/Humility dimension, in particular, is of interest (Anglim & O'Connor, 2019), as previous research has found that Honesty/Humility relates to prosocial behavior (Fang, Dong, & Fang, 2019; Lee & Ashton, 2013; Zettler & Hilbig, 2015). The HEXACO‐PI will allow for the examination of a key personality trait that may have effects on NPO advertising outcomes but has not been previously explored.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research found that Honesty/Humility is predictive of prosocial behavior (Lee & Ashton, 2013; Zettler & Hilbig, 2015). Fang et al (2019) determined that “perspective taking” mediates the relationship between Honesty/Humility and prosocial behavior. Essentially, when people scoring higher in Honesty/Humility observe someone needing help, they are driven to assist through feelings of empathy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These instruments usually detect basic types of prosocial behavior, where they are missing, indicators already incorporated by us, which are already noticeable at this age. Honesty is positively related to prosocial behavior (Ashton, Lee, 2007, Fang, Dong, Fang, 2019. Humility is a prediction and has a positive connection with prosocial behavior (Ashton, Lee, 2007, Allgaier, Zettlera, Wagnerb, Püttmannb, Trautwein, 2015, Fang, Dong, Fang, 2019.…”
Section: Current State Of the Researched Issuesmentioning
confidence: 99%